O sistema do livre convencimento motivado no processo penal em face do ordenamento constitucional - Yuri Alvarenga Maringues de Aquino (2016)
The present work aims to analyze the system of free evaluation of the evidence, adopted in Brazil as a weighing method of evidentiary elements in the criminal procedure, in light of the Republican Constitution, demonstrating the historical and dogmatic basis on which the mentioned system was built. As consequence, it was possible to verify that the writings of legal scholars regarding this subject, as well as the judicial decisions, contradict with the constitutional model of criminal procedure established in the Brazilian Magna Charta, favoring the perpetuation of inquisitorial structures. In this sense, it proposes a reanalysis of the concept of free evaluation of evidence as an authentically democratic mechanism, indispensable for the preservation of fundamental rights settled in the Constitution.